Role of Anesthesia in Reducing Artifacts in Claustrophobic and Infant Patients undergoing MRI - Jadoon, Hassan Khan; Bilal, Rizwan; Baqir Hassan, Khuwaja Muhammed; Aquil, Hafsa; Shehzadi, Zainab; Khan, Junaid (Pakistan Armed Forces Medical Journal, 2026)
Objectives: To determine the role of anesthesia in reducing artifacts in claustrophobic and infant patients undergoing MRI.Study Design:  Cross-sectional study.Place and Duration of Study: Armed Forces Institute of Radiology and Imaging, Rawalpindi Pakistan, from Apr 2023 to Sep 2023.Methodology: Study included 385 claustrophobic and infant patients undergoing MRI. In collaboration with Anesthesia department, claustrophobic and infant patients were given anesthesia. For infant patients, General Anesthesia was given, induction of anesthesia was given by Propofol, and maintenance of anesthesia was through Sevoflurane. Adults 18 years or above, cooperative patients and only history of claustrophobia were administered anesthesia through sedatives e.g Dormicum (Midazolam). Artifacts if present were calculated. SPSS version 26.0 was used to record, enter, and analyze the data.Results:  out of 385 patients, 195(50.6%) were male and 190(49.4%) were female. MRI results showed that 369(95.8%) of the scan had no artifacts, while 16(4.1%) of the patients had artifacts in their MRI scan. In term of complications only 4(1.03%) had mild complications like allergic responses, vomiting, and nausea.Conclusion: The study here concluded that anesthesia have positive role in reducing artifacts in claustrophobic and infant patients undergoing MRI.